The politics of neoliberalism and social justice: Towards a pedagogy of critical locational encounter. (November 2018) - Hager, Tamar; Peyrefitte, Magali; Davis, Carole
The neoliberalisation of higher education is gathering pace and momentum on a global scale, albeit with national differences. In this context, a number of challenges and conflicting politics are emerging especially in relation to pedagogical ethos of social justice. Our article analyzes the general characteristics of neoliberal policy and practices worldwide, looking in particular at their impacts on students and teachers alike mainly in relation to the license to exercise critical thinking and social justice. Subsequently, it suggests resisting neoliberal agenda by using radical teaching methods which consider diversity and difference as social and political assets which allow meaningful dialogue across social, ethnic, national and gender groups while working to promote equality and social justice. This theoretical background informs the five papers composing this Special Issue. The authors all introduce radical and critical research and pedagogies with a struggle for social justice and against inequalities at their core—as effective tools of resistance against the oppressive and unjust conditions created by the neoliberal agendas that are structuring education worldwide. Situated in a range of national contexts, the papers provide the ground for a pedagogy of critical locational encounter, recognizing this as a site of struggle while addressing multiple and complex relationships of power and their contestation.